Field reaction of red fleshed Saccharum robustum against sugarcane borers and termites - Punithavalli, M; Salin, K P; Jebamalaimary, A; Saravanan, L (Indian Journal of Plant Protection, 2022)
Field experiments were conducted to screen the red fleshed Saccharum robustum progenies and along with some popular sugarcane varieties against sugarcane shoot borer, Chilo infuscatellus, internode borer, Chilo sacchariphagus indicus and termites for the two consecutive years (2018-19 and 2019-20) at Sugarcane Breeding Institute, Coimbatore, Tamil Nadu. Among 20 red - fleshed S. robustum progenies screened against shoot borer, 4, 10 and 6 progenies were grouped as tolerance, moderately tolerance and susceptible, respectively. In the progenies, GUK 14-722, GUK 14-130, GUK 14 -129 and GUK 14- 745 were recorded <15% shoot borer incidence which grouped as tolerance genotypes. In the popular sugarcane varieties, C. infuscatellus incidence was lower in Co 06022 and Co 06030. Likewise, only two clones (GUK 14-722 and GUK 14-129) were grouped as tolerance; six clones as moderately tolerance and 12 clones as susceptible to C. sacchariphagus indicus. Approximately, eleven progenies were recorded 6-9% internode borer intensity. The incidence of termites ranged between 21.03 to 75.63% on the red fleshed S. robustum progenies and 2.55 to 11.23% in the popular sugarcane varieties. More than half of the progenies seedlings were infested with > 50% incidence of termites whereas <10% incidence in the popular varieties. The present study identified the genotypes viz., GUK 14-722, GUK 14-130, GUK 14 -129 and GUK 14-745 were tolerance to C. infuscatellus, C. sacchariphagus indicus and termites and these elite genotypes could be used as donors in the future sugarcane breeding programme for the development of borers resistant varieties